If the boot fits - Witemeyer, Karen (Witemeyer, Karen. Texas ever after., 2024)
"When Samantha Dearing's rancher father hosts a ball to find her a husband, she balks at the prospect of marrying a man not of her own choosing. After a mystery guest saves her brother's life and then disappears, leaving only his boot behind, her search for its owner leads to an ending more enchanting than she imagined"--